A hangover like any other: the cost of ruling for populist parties - Andreas Bergh; Anders Kärnä (Public Choice, 2026)
Abstract Populist parties have grown rapidly in popularity in many European countries and have increasingly become common in government coalitions. Because these parties often make expansive promises and derive much of their appeal from their outsider status, entering government may become an electoral liability by the next election. Analyzing populist and mainstream parties in 32 European countries from 1980 to 2023, we estimate the average electoral effect of government participation. We find a post-power penalty of about 4.5–5 percentage points on average. This penalty is remarkably similar for populist and mainstream parties, suggesting that populist parties do not suffer an additional electoral cost from governing. Moreover, the size of the post-power penalty does not vary systematically with growth, inequality, social spending, globalization, or unemployment during the governing term. These findings suggest that bringing populist parties into government does not, by itself, impose a distinctive electoral cost on them relative to other incumbent parties.